Recent and future Colorado water: snow drought, streamflow, and winter recreation - Pfohl, Anna K. D., author; Fassnacht, Steven R., advisor; Barnard, David M., committee member; Kampf, Stephanie K., committee member; Rasmussen, Kristen L., committee member (Colorado State University. Libraries, 2023)
Water in the western United States is a crucial resource for ecosystems, the abiotic environment, and people (for industrial, agricultural, and residential purposes). A majority of this water originates in the seasonal snowpack in the mountains. The snowpack is responsible for maintaining the water supply, and changes to this system have broad and severe implications. Various metrics have been used to quantify these patterns when snow is less than normal, often referred to as a snow drought or a low snow year. In recent decades, the number of years with low snow have increased, and this will continue and intensify into the future. With observed decreases in long-term snow and modeled decreases for the future, high snow years become more critical to support the water supply. Beyond supplying water for downstream use, the seasonal snowpack also sustains the winter recreation industry, which is a large component of many local and state economies. The Weather Research and Forecasting Model (WRF) is a 4-km mesoscale model that can capture orography and convective processes over complex terrain. WRF includes two time periods: the control (CTL) based on historic conditions and the future under pseudo-global warming (PGW) conditions. This dataset was used to drive SnowModel (WRF-SM) to produce 100-m, daily snow water equivalent (SWE), total precipitation, solid precipitation, snowmelt, runoff, and air temperature. Using these datasets, this research examines past and future snow and streamflow in Colorado. We evaluated 1) common metrics and trends for snow drought; 2) used WRF data to drive the Ages hydrologic model to examine changes (snow, streamflow, and flow partitioning) in two high snow years; and 3) ski opportunities at nine different resorts. To evaluate methods of defining snow drought, we used SWE and winter precipitation data from Snow Telemetry stations and the WRF-SM dataset described above. Classifying drought with the ratio of SWE to winter precipitation resulted in drought occurrence for more than 50% of station-years from 1981 to 2020. Using percentiles of long-term peak SWE indicated that occurrence of low or very low years increased from 2001 to 2020 compared with the previous 20 years. Under PGW conditions, elevations between 1800 and 2400 m shifted drought classification towards low or very low, with higher elevations (3200 m and above) remaining relatively unchanged. To examine changes in snow, streamflow, and flow partitioning under a PGW scenario for two high snow years (2008 and 2011), we used Ages, a spatially distributed watershed model, in the Upper Blue River watershed in central Colorado. Changes in snow (snowmelt and solid precipitation) were greatest in magnitude at high elevations. Timing of peak streamflow shifted to nearly two months earlier under a PGW scenario. To examine ski opportunities, we developed metrics to quantify ski conditions. The number of opportunities for snowmaking in the future will decrease throughout the season, but especially in October and November. Ski days (snow depth greater than 50 cm) will decrease in early and late season and increase at lower elevations from January through March. Powder days (fresh depth greater than 15 cm and fresh density greater than 125 kg/m3) follow a similar pattern. Ski resorts at low elevations will generally be more susceptible to changes under a PGW scenario. Additionally, using a fine-resolution dataset allowed investigation of smaller study areas to understand the changes that are not captured with coarser resolutions.